¿Qué piensa el profesorado de una comunidad autónoma acerca de su formación tras un cambio educativo? - Marrero Galván, Juan José; Fernández González, José; Tejera Rodríguez, Carmelo; Elórtegui Escartín, Nicolás (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2012)
El presente trabajo se centra en cómo ha evolucionado el pensamiento de los profesores de Ciencias experimentales sobre su desarrollo profesional, durante el periodo que coincide con distintas leyes educativas. La investigación consta de dos estudios similares realizados en 2002 y 2011, fundamentados en investigaciones anteriores. El análisis de los resultados y su comparación nos deparan una serie de conclusiones que ponen de manifiesto qué aspectos de las opiniones del profesorado han cambiado y cuáles permanecen. Palabras clave: pensamiento profesor, ciencias experimentales, educación secundaria, formación y perfeccionamiento del profesorado. What do teachers of an autonomous region think about their training after an educational change? This work is centred on how the teachers´ thought has evolved. It is focused on experimental science teachers in the Canary Island Autonomous Region (Spain). It is also about the professional development during a time lapse that coincides with different educative laws. In this work, there are two stages. At the first stage, it is designed and elaborated a poll on the teachers´ formation and training, based in an opinion poll in 2002 and 2011. The results are studied and they give us some conclusions which clearly remark what aspect of the teachers´ opinions have changed and which ones still haven´t changed. Then, at a second stage it is compared the results with similar questions that were investigated by some authors in 1988 and 1989 so we can now compare the teachers´ opinion, in different moments, on the most important aspects related to their formation and training. Keywords: teacher thinking, experimental sciences, secondary education, teacher formation and training.